Essaie de Description du SystÃ¨me Foncier Congolais dâ€™avant Le Contact Formel Avec La Civilisation Occidentale - Lonu, Marie-Bernard Dhedya; Gehrin, Markus; Cordonier, Marie-Claire; Moke, Michel Ilume; Wabassa, Salomon Mampeta (European Scientific Journal, ESJ, 2017)
The present study focuses on the description of the Congolese land system prior to formal contact with Western civilization. Contrary to what has been imagined, the natives of Congo have understood the notion behind landed property. This property is rather peculiar in that it does not fulfill all the criteria imposed by modern law. A few elements have enabled us to describe it. The notion of landed property has been made known to the natives. This property is established at the moment the pacific takes possession of it or by conquest of the soil. It is essentially influenced by the beliefs that characterize traditional Africa. However, the beliefs in the existence and interaction of the world of the dead with that of the living, and the beliefs in the divinity of the soil, makes it possible to specially guide the perception of landed property. Moreover, the community character directs land ownership towards collective ownership rather than individual ownership.